The Review of Insulin Pens—Past, Present, and Look to the Future - Masierek, Małgorzata; Nabrdalik, Katarzyna; Janota, Oliwia; Kwiendacz, Hanna; Macherski, Maksymilian; Gumprecht, Janusz (Frontiers in Endocrinology, 2022)
Currently, there are about 150-200 million of diabetic patients treated with insulin globally. The year 2021 is special because 100th anniversary of the insulin discovery is being celebrated. It is a good occasion to sum up the insulin pens technology invention and improvement which are nowadays the leading mode of an insulin delivery. Even though so many years have passed, insulin is still administered subcutaneously that is why devices to deliver it are of great importance. Insulin pens have evolved only through the last decades (the reusable, durable pens, and the disposable, prefilled pens) and modern smart insulin pens have been developed in the last few years and both types of the devices compared to traditional syringes and vials are more convenient, discrete in use, have better dosing accuracy, and improve adherence. In this review we will focus on the history of insulin pens and their improvement over the previous decades.